Evaluation of the Antiviral Activity of Drugs from the Group of Polymer Electrolyte Derivatives against a Wide Range of Viruses - D. N. Razgulyaeva; A. M. Klabukov; A. V. Galochkina; A. V. Garshinina; O. N. Zhuravskaya; I. I. Gavrilova; V. A. Manakhov; N. A. Nesterova; A. A. Shtro; E. F. Panarin (Антибиотики и Химиотерапия)
Background. The modern healthcare system is constantly improving and introducing new measures to protect the population from viral diseases, but the experience of the COVID-19 pandemic has shown that infections cannot always be controlled on global scale. In this regard, the development of new broad-spectrum antiviral drugs is more relevant than ever.The aim of the study was to investigate the antiviral activity and cytotoxicity of copolymers of sodium styrene sulfonate and vinyl monomers of various chemical structures, as well as to identify promising polymers for the development of new antiviral agents.Materials and methods. 14 copolymers of sodium styrene sulfonate (NaSS) with various functional comonomers were synthesized. Three viruses with different reproduction strategies and transmission methods — respiratory syncytial virus, influenza virus, and herpes virus — were selected for the assessment of antiviral activity.Results. The screening identified copolymers that showed high activity against all three viruses. It was found that the introduction of various functional groups into the structure of NaSS did not decrease antiviral activity, but significantly reduced cytotoxicity. The molecular weight has also shown a noticeable effect on the activity. Different sensitivity of viruses and cells to the studied polymers was revealed, likely due to the structural features of the virus shell and cell wall.Conclusions. The results demonstrate the potential of sodium styrene sulfonate copolymers as a model for developing a broad-spectrum antiviral drug.